Moral values ​​for the Civic-Military Schools: heteronomy as educational project - Daud, Rafael Pétta (2023)
The present work intends to understand some aspects of the educational project underlying the implementation of Civic-Military Schools (ECIM) by the Bolsonaro government. To do so, we submitted to a hermeneutic analysis the moral values ​​that, accompanied by the respective descriptors, are postulated by the Guidelines for Civic-Military Schools as a norm for ECIM: civility, honesty and respect. We conclude that such values, in the way they are situated, represent a strong predilection for moral heteronomy as an educational principle, distancing themselves, therefore, from the moral autonomy that would be favored by the democratization of school relations.